Phosphogypsum-based phase change energy storage wallboard as well as preparation method and application thereof
By combining LA-HD-PA/DME fixed phase change material with modified porous diatomaceous earth and mixing it with phosphogypsum, cement and fly ash, composite phase change energy storage gypsum board is prepared, which solves the problems of easy leakage of existing materials and poor insulation effect, and achieves efficient heat insulation and thermal stability, which is suitable for energy saving and consumption reduction in building walls.
Patent Information
- Application Number
- CN202510259215.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-02
- Filing Date
- 2025-03-06
- Publication Date
- 2025-05-09
AI Technical Summary
Existing phosphogypsum-based composite phase change energy storage materials are prone to leakage during use, and the high thermal conductivity leads to poor insulation effect, which is not suitable for energy saving and consumption reduction in building walls.
Composite phase change energy storage gypsum board is prepared by combining LA-HD-PA/DME shaped phase change material with modified porous diatomaceous earth and mixing it with phosphogypsum, cement and fly ash to ensure stable bonding of the material and good thermal insulation performance.
The composite phase change energy storage gypsum board has achieved simple and integrated molding, with good thermal insulation performance and thermal stability, no leakage, effectively improving indoor comfort and reducing energy consumption, and verifying its heat storage and heat dissipation capabilities and temperature control effects through the micro room model.
Smart Images

Figure CN119954482A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building energy conservation, and in particular to a phosphogypsum-based phase-change energy storage wallboard and a preparation method and application thereof. Background Art
[0002] Traditional building materials often have difficulty maintaining a comfortable indoor environment under extreme weather conditions, while phase change energy storage wall panels provide an efficient solution that helps improve the energy efficiency of buildings, significantly reduce energy demand for air conditioning and heating, reduce living costs and greenhouse gas emissions in building operations, and develop phase change energy storage materials with good heat storage capacity, strong temperature regulation ability, and high flexural and compressive strength. It is a hot topic of research. Phosphogypsum-based phase change energy storage wall panels are an innovative building material that combines the structural strength of traditional phosphogypsum boards with the unique thermal energy storage properties of phase change materials. When the ambient temperature changes, the material can absorb or release heat through the phase change process, thereby effectively maintaining the stability of the indoor temperature. Phase change energy storage phosphogypsum boards mainly include: organic phase change phosphogypsum boards, inorganic phase change phosphogypsum boards, and composite phase change phosphogypsum boards. Organic phase-change phosphogypsum board has high heat storage capacity and good phase-change stability, but may face environmental and health risks of high-temperature volatilization; inorganic phase-change phosphogypsum board has good thermal conductivity and strong stability, and is suitable for a variety of buildings, but phase separation may occur at low temperatures; composite phase change combines the advantages of organic and inorganic, improves the flexibility of performance, but its production process is complicated, the production cost is relatively high, and the phase change material is prone to leakage during use. For example, the production process of phase-change thermostatic diatom board is complicated, and different raw materials need to be used to make the surface layer and the middle layer respectively, and then the surface layer and the middle layer are bonded together with a binder to obtain a preformed board. In the prior art phosphogypsum-based composite phase-change energy storage material, phosphogypsum is directly mixed with the phase change material, and leakage is prone to occur during use. This is because the phase change material will become liquid after being heated and seep out of the porous phosphogypsum. The thermal conductivity of the composite material is too high at 0.505W / (mK), and the thermal insulation effect is poor, which is not suitable for energy saving and consumption reduction of building walls.
[0003] The above information disclosed in this Background section is only for enhancement of understanding of the background of the invention and therefore it may contain information that does not form the prior art that is already known to a person of ordinary skill in the art. Summary of the invention
[0004] The present invention provides a phosphogypsum-based phase change energy storage wallboard and its preparation method and application. LA-HD-PA / DME shaped phase change material is added to phosphogypsum in different proportions, and mixed with building materials such as cement and fly ash to prepare a composite phase change energy storage gypsum board. The multi-element phase change material (LA-HD-PA) is compounded with modified porous diatomaceous earth (DME) by vacuum adsorption method, which ensures the stable combination of LA-HD-PA and DME without leakage. The mass ratio is LA-HD-PA: MDE=45:55. Diatomaceous earth (DEM) is low in price, easy to obtain, energy-saving and environmentally friendly. In summary, the composite phase change energy storage gypsum board has a simple manufacturing process, integrated molding, good thermal insulation performance and thermal stability, and will not leak. The heat storage and heat release capacity and temperature control effect of the phase change wallboard are verified by a self-made micro-room model, which can effectively improve indoor comfort, reduce energy consumption and improve environmental control, and provide an innovative solution for sustainable building design.
[0005] The preparation method of phosphogypsum-based phase change energy storage wallboard comprises: Step 1: Weigh lauric acid-hexadecanol-palmitic acid LA-HD-PA and modified diatomaceous earth DME according to a predetermined mass ratio; Step 2: placing the modified diatomaceous earth DME in a first temperature constant temperature dryer to a constant weight, heating the lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA solid to a liquid state and then adding the solid to the dried modified diatomaceous earth to form a mixture; Step 3: Stirring the mixture at a second temperature for a first predetermined time and then placing it in a vacuum drying oven for vacuum drying, and then taking it out and grinding it after a second predetermined time to obtain a diatomite-based shaped composite phase change material LA-HD-PA / DME; Step 4: Add the diatomite-based shaped composite phase change material LA-HD-PA / DME into phosphogypsum according to a predetermined mass ratio, and mix it with cement and fly ash to prepare a composite phase change energy storage gypsum board.
[0006] In the preparation method of the phosphogypsum-based phase change energy storage wallboard, the predetermined mass ratio is lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA: modified diatomaceous earth DME=45:55.
[0007] In the preparation method of the phosphogypsum-based phase-change energy storage wallboard, diatomaceous earth is subjected to roasting, acid washing and alkali washing to obtain modified diatomaceous earth.
[0008] In the preparation method of the phosphogypsum-based phase change energy storage wallboard, the first temperature is 120°C and the second temperature is 80°C.
[0009] In the method for preparing the phosphogypsum-based phase change energy storage wallboard, the first predetermined time is 20 minutes and the second predetermined time is 2 hours.
[0010] In the preparation method of the phosphogypsum-based phase change energy storage wallboard, the mixture is poured into a beaker, and the beaker containing the mixture is placed in a vacuum drying oven for vacuum drying, and the vacuum drying oven is set at a temperature of 80° C. and a vacuum degree of 0.08 MPa.
[0011] In the preparation method of the phosphogypsum-based phase-change energy storage wallboard, under a vacuum state, capillary force and intermolecular force adsorb liquid lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA into the pores of the modified diatomaceous earth.
[0012] In the preparation method of the phosphogypsum-based phase change energy storage wallboard, the predetermined mass proportion of the diatomaceous earth-based shaped composite phase change material LA-HD-PA / DME in the total mass is 5%-20%. A phosphogypsum-based phase-change energy storage wallboard is produced by a preparation method of a phosphogypsum-based phase-change energy storage wallboard.
[0013] Phosphogypsum-based phase change energy storage wallboard is used in building walls.
[0014] Compared with the prior art, the present invention has the following advantages: the present invention uses phosphogypsum as the main matrix material of the wallboard, and mixes LA-HD-PA / DME shaped phase change material (LA-HD-PA is compounded with modified DME by vacuum adsorption method to ensure the stable combination of LA-HD-PA and DME, and the mass ratio is LA-HD-PA: MDE=45:55) into phosphogypsum in different proportions, and mixes with building materials such as cement and fly ash to prepare phase change energy storage gypsum board. The production process is simple, and the integrated molding is used. The obtained energy storage gypsum board has good thermal insulation performance and thermal stability, and will not leak. The heat storage and heat release capacity and temperature control effect of the phase change wallboard are also verified by a self-made micro-room model. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work. Moreover, the same reference numerals are used to represent the same components throughout the drawings.
[0016] In the attached picture: Figure 1 It is a schematic diagram of the appearance of the phase change energy storage gypsum board PCGB-0, PCGB-1, PCGB-2, PCGB-3, and PCGB-4 of the present invention, wherein: Figure 1 (a) Schematic diagram of the appearance of phase change gypsum board PCGB-0, Figure 1 (b) Schematic diagram of the appearance of phase change gypsum board PCGB-1. Figure 1 (c) Schematic diagram of the appearance of phase change gypsum board PCGB-2. Figure 1 (d) Schematic diagram of the appearance of phase change gypsum board PCGB-3. Figure 1 (e) Schematic diagram of the appearance of phase change gypsum board PCGB-4; Figure 2 The morphological structure diagram of PCGB-0, PCGB-1, PCGB-2, PCGB-3 and PCGB-4 of the present invention is magnified 400 times under electron microscope scanning, wherein: Figure 2 (a) Schematic diagram of the morphology and structure of the phase change gypsum board PCGB-0 at 400X magnification. Figure 2 (b) Schematic diagram of the morphology and structure of the phase change gypsum board PCGB-1 at 400X magnification. Figure 2 (c) Schematic diagram of the morphology and structure of the phase change gypsum board PCGB-2 at 400X magnification. Figure 2 (d) Schematic diagram of the morphology and structure of the phase change gypsum board PCGB-3 at 400X magnification. Figure 2 (e) Schematic diagram of the morphological structure of the phase change gypsum board PCGB-4 at 400X magnification; Figure 3 Schematic diagram of thermal conductivity curves of PCGB-0, PCGB-1, PCGB-2, PCGB-3 and PCGB-4; Figure 4 FT-IR diagram of LA-HD-PA, DME and LA-HD-PA / DME of the present invention. FT-IR is Fourier transform infrared spectrometer, Figure 4 (a) Schematic diagram of the specific heat capacity curve of PCGB-0, Figure 4 (b) Schematic diagram of the specific heat capacity curve of PCGB-1. Figure 4 (c) Schematic diagram of the specific heat capacity curve of PCGB-2. Figure 4 (d) Schematic diagram of the specific heat capacity curve of PCGB-3. Figure 4 Middle (e) Schematic diagram of the specific heat capacity curve of PCGB-4; Figure 5 It is a schematic diagram of the thermal decomposition curve of pure gypsum board; Figure 6 Schematic diagram of thermal decomposition curves of PCGB-1, PCGB-2, PCGB-3 and PCGB-4 of the present invention; Figure 7 This is a schematic diagram of the temperature-time curve of the light energy storage of the phase-change gypsum board of the present invention. Figure 7 (a) Temperature-time curve of PCGB-0 phase change energy storage gypsum board under light irradiation. Figure 7 (b) Temperature-time curve of PCGB-1 phase change energy storage gypsum board under light irradiation. Figure 7 (c) Temperature-time curve of PCGB-2 phase change energy storage gypsum board under light irradiation. Figure 7 (d) Temperature-time curve of PCGB-3 phase change energy storage gypsum board under light irradiation. Figure 7 Middle (e) Light storage temperature-time curve of PCGB-4 phase change energy storage gypsum board.
[0017] The present invention is further explained below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0019] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0020] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0021] like Figures 1 to 7 As shown, the preparation method of phosphogypsum-based phase change energy storage wallboard includes the following steps: Step 1: Weigh lauric acid-hexadecanol-palmitic acid LA-HD-PA and modified diatomaceous earth DME according to a predetermined mass ratio; Step 2: placing the modified diatomaceous earth DME in a first temperature constant temperature dryer to a constant weight, heating the lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA solid to a liquid state and then adding the solid to the dried modified diatomaceous earth to form a mixture; Step 3: Stirring the mixture at a second temperature for a first predetermined time and then placing it in a vacuum drying oven for vacuum drying, and then taking it out and grinding it after a second predetermined time to obtain a diatomite-based shaped composite phase change material LA-HD-PA / DME; Step 4: Add the diatomite-based shaped composite phase change material LA-HD-PA / DME into phosphogypsum according to a predetermined mass ratio, and mix it with cement and fly ash to prepare a composite phase change energy storage gypsum board.
[0022] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, the predetermined mass ratio is lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA: modified diatomaceous earth DME=45:55.
[0023] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, the diatomaceous earth is subjected to roasting, acid washing and alkali washing to obtain modified diatomaceous earth.
[0024] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, the first temperature is 120°C and the second temperature is 80°C.
[0025] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, the first predetermined time is 20 minutes and the second predetermined time is 2 hours.
[0026] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, the mixture is poured into a beaker, and the beaker containing the mixture is placed in a vacuum drying oven for vacuum drying, and the vacuum drying oven is set to a temperature of 80° C. and a vacuum degree of 0.08 MPa.
[0027] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, under a vacuum state, capillary force and intermolecular force adsorb liquid lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA into the pores of the modified diatomaceous earth.
[0028] In a preferred embodiment of the method for preparing the phosphogypsum-based phase change energy storage wallboard, the predetermined mass proportion of the diatomaceous earth-based shaped composite phase change material LA-HD-PA / DME in the total mass is 5%-20%. A phosphogypsum-based phase-change energy storage wallboard is manufactured by the phosphogypsum-based phase-change energy storage wallboard preparation method.
[0029] Phosphogypsum-based phase change energy storage wallboard is used in building walls. In one embodiment, the thermally conductive filler added in step 4 includes but is not limited to one or more one-dimensional or two-dimensional thermally conductive fillers selected from expanded graphite, foamed carbon, nanosilver fiber, nanocarbon fiber, chopped carbon fiber, carbon felt, carbon fiber felt, single-walled or multi-walled carbon nanotubes, graphene, and MXene.
[0030] In one embodiment, the production process of phosphogypsum-based phase change energy storage wallboard is as follows: Using phosphogypsum as the building base material, cement and fly ash as the cementitious materials, and introducing LA-HD-PA / DME shaped phase change material, polycarboxylate water reducer and gypsum retarder, phase change energy storage gypsum boards with LA-HD-PA / DME shaped phase change material mass proportions of 0%, 5%, 10%, 15%, and 20% were prepared. The properties of the materials used are as follows: (1) Phosphogypsum: purchased from Gongyi Yuanheng Water Purification Material Factory. Its main component is calcium sulfate dihydrate (CaSO4·2H2O), which usually contains a small amount of unreacted phosphoric acid, fluoride and other impurities. It has a low density and good hydraulic hardness. It is widely used in the production of building materials such as gypsum boards and blocks. It also plays a role in soil improvement and agricultural fertilizers.
[0031] (2) Cement: Ordinary Portland cement P·O 42.5 grade was purchased from Zhengzhou Lanke Environmental Protection Water Purification Material Factory. The cement parameters are shown in Table 1.
[0032] Table 1 Basic physical and mechanical properties of cement (3) Fly ash: Class II fly ash, purchased from Zhengzhou Hengyuan New Materials Co., Ltd., with a moisture content of 0.32%, a 7d activity index of 81.23%, and a 28d activity index of 85.3%. The main mineral components are α-quartz, mullite, and glass. The chemical composition is shown in Table 2.
[0033] Table 2 Chemical composition of fly ash (%) (4) Polycarboxylic acid water reducer: purchased from Yuncheng Weike Building Materials Co., Ltd., it has the characteristics of high water reduction rate, good fluidity, safety and environmental protection. The specific performance parameters are shown in Table 3.
[0034] Table 3 Performance parameters of polycarboxylate water reducer (5) Gypsum retarder: purchased from Beijing Kaili Tianwei Technology and Trade Co., Ltd., milky white powder solid, easily soluble in water, and highly stable. The effect of the amount of retarder added on the setting time and flexural / compressive strength of gypsum board (water-to-cement ratio of 5:4, temperature 20°C, relative humidity of air 45%~65%) is shown in Table 4.
[0035] Table 4 Parameters affecting the performance of desulfurized gypsum board by retarder dosage The specific production process of phosphogypsum-based phase change energy storage wallboard is as follows: Step 1, prepare a 200×200×50mm mold and apply a release agent; Step 2, accurately weigh the required materials according to the material ratio listed in Table 5, and pour them into a beaker and mix them evenly; Step 3, add deionized water to the beaker according to the water-to-material ratio of 0.4, and stir for 10 to 15 minutes to ensure that the water fully penetrates the gypsum powder; Step 4, evenly apply an oily release agent on the inner wall of the 200mm×200mm×50mm mold; Step 5, mix the evenly stirred slurry The material is injected into the mold, leveled and compacted, and the gypsum test boards with a mass percentage of 0% to 20% of the shaped phase change material are numbered PCGB-0 to PCGB-5 respectively; the sixth step is the demoulding operation. After the gypsum slurry is poured into the mold, it will solidify and release heat. After about 6 hours, it will completely harden and can be demoulded at this time; the seventh step is to place the demoulded gypsum test board in a standard curing box. The curing environment is maintained at a temperature of 20±1℃ and a humidity of 65%±5% until the predetermined curing period is met. The preparation of the phase change energy storage gypsum board is completed. Figure 1 As shown, the prepared phase change gypsum boards are named PCGB-0, PCGB-1, PCGB-2, PCGB-3, and PCGB-4 respectively.
[0036] Table 5 Material mix ratio of phosphogypsum-based phase change energy storage wallboard Comprehensive performance analysis of phase change energy storage gypsum board Micromorphology analysis The microstructure of the composites and the dispersion of phase transition in cement matrix were studied by scanning electron microscopy. Figure 2 The morphological structures of PCGB-0, PCGB-1, PCGB-2, PCGB-3, and PCGB-4 are shown at 400 times magnification. Figure 2 It can be seen that the structure of pure phosphorus gypsum board is relatively tight, and the number of exposed large pores is relatively small. However, when the proportion of fixed phase change material increases, the larger the pores inside it, the worse the overall density. This is mainly because the fixed phase change material has low density, low strength, and is porous, which makes its support ability for the skeleton far less than that of pure gypsum sheets. After mixing with phosphorus ash paste and cement, more voids will be produced. On the other hand, the fixed phase change material can be better mixed with phosphorus gypsum, cement, fly ash, etc. without any leakage, which means that it can exist in the gypsum board in its original form and be used in building walls to exert its own phase change energy storage characteristics to achieve energy-saving effects.
[0037] Thermal performance analysis DSC was used to test the thermal properties of PCGB-0, PCGB-1, PCGB-2, PCGB-3 and PCGB-4. Table 6 shows the DSC thermal properties of the above four specimens during the heating process. It can be seen that PCGB-0 does not contain a shaped phase change composite material, so it does not have a phase change endothermic peak and a phase change temperature. The phase change peak temperatures of PCGB-1, PCGB-2, PCGB-3 and PCGB-4 are 24.844℃, 25.207℃, 25.774℃ and 24.642℃, respectively, indicating that the thermal performance of the shaped phase change material LA-HD-PA / DME is relatively stable, and the phase change peak temperature does not fluctuate much. In addition, the melting temperature of the shaped phase change composite material after DSC testing is 27.75℃, and the phase change peak temperature after mixing with building materials such as phosphogypsum is significantly reduced. The reason is that the hydration products of the building materials after hydration re-encapsulate the shaped phase change composite material. From the latent heat values of PCGB-1, PCGB-2, PCGB-3 and PCGB-4 in the table, it can be seen that the latent heat value of phase change increases with the increase of the content of shaped composite phase change material, and the latent heat of phase change of wallboard with only 5% content of phase-shaped phase change material is only 2.503J / g, while the latent heat of phase change gypsum board with 10%, 15% and 20% content of shaped phase change material is 2.515 times, 3.47 times and 4.62 times of that, indicating that the latent heat value of phase change energy storage wall is proportional to the content of shaped composite phase change material. This is because the shaped composite phase change material in the wall significantly increases the heat capacity of the wall, and the shaped composite phase change material is added to the cementitious material in equal proportion to replace fly ash, and the density of the cementitious material decreases accordingly, so the growth rate of the latent heat value of phase change is greater than the increase in the content of shaped composite phase change material.
[0038] Table 6 Thermophysical properties of PCGB-1, PCGB-2, PCGB-3 and PCGB-4 Thermal conductivity analysis The thermal conductivity of PCGB-0, PCGB-1, PCGB-2, PCGB-3 and PCGB-4 was tested using a thermal conductivity tester. The test results are as follows: Figure 3 shown. Figure 3The thermal conductivity of PCGB-0 was measured to be 0.3753W / (m·K), and the thermal conductivity of PCGB-1 to PCGB-4 decreased to 0.3316W / (m·K), 0.3047W / (m·K), 0.2863W / (m·K) and 0.2634W / (m·K), respectively, which were reduced by 11.6%, 18.8%, 23.7% and 29.8% compared with PCGB-0. The analysis data showed that when the content of the shaped phase change material in the specimen gradually increased, the thermal conductivity of the phase change energy storage wall showed a trend of gradual decrease. This is because the thermal conductivity of the shaped phase change material is lower than that of cement and fly ash, and it replaced the corresponding proportion of fly ash in PCGB-1 to PCGB-4. As the content of the shaped phase change material increases, the amount of fly ash replaced also increases. Since the thermal conductivity test is carried out at room temperature, the shaped phase change material absorbs heat during the phase change process, resulting in a decrease in the thermal diffusivity of the wall, and the thermal diffusivity is positively correlated with the thermal conductivity, so the thermal conductivity of the phase change energy storage wall panel is reduced accordingly. This shows that the phase change energy storage wall not only has the ability to store and release heat, but also has good thermal insulation performance, meeting the application requirements of actual projects. Specific heat analysis like Figure 4 As shown in the figure, the specific heat capacity of the phase-change energy storage gypsum board increases with the increase of the content of the shaped phase change material. When the temperature is the phase change peak temperature of the phase-change gypsum board, that is, around 25°C, different contents of the shaped phase change material have a significant effect on the specific heat capacity of the gypsum board. In the figure, the specific heat capacity of the phase-change thermal storage foam concrete with the content of 0%, 5%, 10%, 15% and 20% of the shaped phase change material is 1021 J / (kg·℃), 1107 J / (kg·℃), 1276 J / (kg·℃), 1352 J / (kg·℃) and 1406 J / (kg·℃), respectively. Compared with the pure phosphogypsum board without shaped phase change material, the specific heat capacity of the phase-change energy storage gypsum board containing 5%, 10%, 15% and 20% of the shaped phase change material increased by 8.42%, 24.9%, 32.4% and 37.8%, respectively. This data shows that as the content of shaped phase change material in gypsum board increases, the specific heat capacity of the board also increases, and its heat storage capacity is also enhanced. Thermal stability analysis The thermal stability of PCGB-0, PCGB-1, PCGB-2, PCGB-3 and PCGB-4 was tested by TG. Figure 5 and Figure 6 The thermogravimetric curves of PCGB-0, PCGB-1, PCGB-2, PCGB-3 and PCGB-4 in the temperature range of 30~400℃. Figure 5 and Figure 6As can be seen from the above, within the test temperature range of 30~120℃, the mass of the five specimens decreased in a small range, and the mass loss rate was within 2%, which was caused by the evaporation of water molecules inside the specimens; within the test temperature range of 120~140℃, the mass of the four specimens decreased rapidly, and the mass loss rate reached about 3.5~4.5%, which was the main weight loss stage. This is because the phosphogypsum dehydrated in this temperature range. Due to the Ca in the phosphogypsum, the mass of the four specimens decreased rapidly, and the mass loss rate reached about 3.5~4.5%, which was the main weight loss stage. 2+ and SO4 2- After the ions are combined, the weaker parts are split with the water molecules, and then anhydrous gypsum is formed after dehydration at high temperature; within the test temperature range of 150~400℃, the mass of PCGB-0 decreases relatively slowly, and the mass loss rate in this heating stage is only about 3% to 4%, mainly because the cement in PCGB-0 is hydrated to form calcium sulfonate, which decomposes at high temperature and causes the mass to decrease. However, the mass decrease of PCGB-1, PCGB-2, PCGB-3 and PCGB-4 in this temperature range is not the same. In general, PCGB-1, PCGB-2, PCGB-3 and PCGB-4 show continuous mass loss, so it can be seen that the thermal weight loss in the phase change gypsum board is mainly caused by the decomposition of LA-HD-PA / DME.
[0039] exist Figure 6 In the TG curves of phase change energy storage gypsum boards PCGB-1, PCGB-2, PCGB-3 and PCGB-4, two obvious mass loss stages can be observed. It can be determined that 148℃ is the dividing point, and the mass loss in the first stage occurs between 30℃ and 148℃. The mass loss in this stage is mainly due to the evaporation of water in the gypsum board and the dehydration and decomposition of substances such as calcium sulfate. In the second stage of thermal weight loss in the temperature range of 148℃ to 400℃, the mass of the phase change gypsum board decreases rapidly, mainly due to the thermal decomposition of LA-HD-PA / DME and the dehydration of cement hydration products. For the phase change gypsum boards containing 5%, 10%, 15% and 20% LA-HD-PA / DME, the mass losses are 8.26%, 8.99%, 10.96% and 11.56%, respectively. This also shows that with the increase of LA-HD-PA / DME content, the mass loss of phase change gypsum board in this temperature range also increases.
[0040] When LA-HD-PA / DME is added to gypsum board, an increase in its thermal weight loss temperature can be observed. This phenomenon can be attributed to the coating effect of gypsum board on the surface of composite phase change material, which slows down the thermal decomposition process of the material to a certain extent. Therefore, this treatment improves the heat resistance of gypsum board. In addition, considering that the outer surface temperature of the building envelope structure usually does not exceed 70 to 80°C, within this temperature range, the gypsum board doped with composite phase change material has almost no obvious mass loss. This shows that the prepared phase change gypsum board has excellent thermal stability in practical applications.
[0041] Analysis of light heat storage capacity of micro room model Infrared heaters were used to simulate solar radiation in outdoor environments, and the temperature changes on the inner and outer surfaces of phase change gypsum boards and inside the micro room model were explored. The heat storage and temperature control performance of phase change energy storage gypsum boards containing different proportions of shaped phase change materials were compared and analyzed. The heat storage and release characteristic curves of the inner and outer surfaces of phase change gypsum test boards with different LA-HD-PA / DME contents are shown in Figure 2. Figure 7 .
[0042] PCGB-0 is pure phosphorus gypsum board, while the LA-HD-PA / DME contents of PCGB-1, PCGB-2, PCGB-3, and PCGB-4 are 5%, 10%, 15%, and 20%, respectively. Therefore, PCGB-0 is used as the control group. Compared with the phase change energy storage gypsum boards with other LA-HD-PA / DME contents, since each gypsum board is heated for 60 minutes, their temperatures start to rise from 20°C. Figure 7In PCGB-0~PCGB-4, it can be observed that the outer surface temperature curve rises to the maximum temperature at a very steep rate with a large slope, but with the increase of LA-HD-PA / DME contained in the phase change energy storage gypsum boards PCGB-0~PCGB-4, the slope of the outer surface temperature curve has a slight change. Compared with PCGB-0, the slope of PCGB-1~PCGB-4 decreases and the maximum temperature becomes smaller. It can be seen from Table 7 that the maximum outer surface temperature of PCGB-1~PCGB-4 boards is successively reduced by 5.3℃, 5.6℃, 6.5℃, and 7.9℃ compared with the control group PCGB-0, and the maximum inner surface temperature is successively reduced by 3.7℃, 4.8℃, 5.4℃, and 7.2℃; the research results show that The gypsum board with LA-HD-PA / DME has better thermal insulation effect than the pure phosphorus gypsum board PCGB-0. The reason is that LA-HD-PA / DME in the gypsum boards of PCGB-1~PCGB-4 absorbs heat and cools down. As the content of LA-HD-PA / DME increases, the specific heat capacity of the gypsum board gradually increases, and the more heat is absorbed, which plays a decisive role in reducing the outer and inner surface temperatures of the board. It can also be seen from the data in the table that the time difference from the outer surface temperature of PCGB-0 rising to the highest to the inner surface temperature rising to the highest is 644s. Compared with PCGB-0, the delay time of PCGB-1~PCGB-4 is increased by 35.6%, 55.9%, 66.5% and 78.5% respectively. It can be seen that the higher the LA-HD-PA / DME content of the plate, the greater its effect in delaying the highest temperature point, and can separate the highest temperature points on the inner and outer surfaces, thereby playing a role in regulating temperature across time, staggering the highest temperature point on the outside of the wall and the highest temperature point on the inner surface, that is, also staggering the highest ambient temperature and the highest indoor temperature. observe Figure 7From the indoor temperature of the PCGB model, we can also know that the temperatures of PCGB-1~PCGB-4 are gradually lower than that of PCGB-0. When the inner surface temperature of PCGB reaches the highest, it will gradually decrease, and the indoor temperature of the PCGB model will also gradually decrease. Since the heat exchange between PCGB and air is in the form of heat convection, the two are not immediately effective, but there is a certain time interval. Therefore, it can be observed that the highest point of the indoor temperature of the PCGB model is earlier than the inner surface temperature of PCGB. Because when the temperature of the inner surface wall panel reaches a high point and then drops, it cannot continue to provide heat to the model room, causing its temperature to continue to rise. Therefore, the highest point of the indoor temperature of the model will be earlier than the highest point of the inner surface temperature of PCGB. Moreover, since PCGB-0 is a pure phosphorus gypsum board and does not have high heat storage performance, the highest point of the indoor temperature of the model will be higher than the highest point of the inner surface temperature of PCGB. The time interval between the highest point in the indoor temperature of the model and the highest point in the inner surface temperature of PCGB is very short, only 128s. Compared with PCGB-0, the time intervals between the highest point in the indoor temperature of the model and the highest point in the inner surface temperature of PCGB of PCGB-1~PCGB-4 are 377s, 506s, 572s and 608s respectively. This is because the LA-HD-PA / DME in the wall panel stores enough heat during the heating process. After the outer surface temperature stops rising, this stored heat can make the inner surface temperature of PCGB continue to rise to the highest temperature for a period of time. As the content of LA-HD-PA / DME in the wall panel increases, more heat is stored in the wall panel, which can make the time interval between the highest temperature of the inner surface temperature of the wall panel and the highest temperature of the indoor temperature of the model longer. This is enough to show that the phase change wall panel with a higher content of composite phase change material can maintain a constant indoor temperature of the building for a longer time, and its heat storage performance is better.
[0043] Table 7 Temperature and temperature difference at each time point of phase change gypsum board PCGB-0~PCGB-4 Scanning electron microscope observations show that the shaped phase change material can better integrate with the building material matrix without obvious leakage. After testing the thermal properties and thermal stability of the phase change energy storage gypsum board specimens using DSC, TG and thermal conductivity tester, it was found that the phase change latent heat value increased with the increase of the content of the shaped composite phase change material, and the phase change latent heat of the wallboard with a content of only 5% of the shaped phase change material was only 2.503J / g, while the latent heat of the phase change gypsum board with a content of 10%, 15%, and 20% of the shaped phase change material was 2.515 times, 3.47 times, and 4.62 times that of the wallboard, indicating that the phase change latent heat value of the phase change energy storage wall is proportional to the dosage of the shaped composite phase change material; compared with the phosphogypsum wallboard without shaped composite phase change material, the specific heat capacity of the phase change energy storage gypsum board with a content of 5%, 10%, 15%, and 20% of the shaped composite phase change material increased by 8.42%, 24.9%, 32.4%, and 37.8%, respectively. This shows that the more the shaped composite phase change material is added to the gypsum board, the greater the specific heat capacity of the board and the stronger the heat storage capacity. However, the increase in the amount of composite phase change material in the specimen will lead to a downward trend in the thermal conductivity of the phase change energy storage gypsum board. In addition, through TG test analysis, the phase change energy storage gypsum board has good thermal stability, and has good thermal insulation properties while having heat storage and heat release characteristics, which meets the actual engineering needs.
[0044] In the temperature control performance test of the micro room model, it was found that with the increase of LA-HD-PA / DME contained in the phase change energy storage gypsum boards of PCGB-0~PCGB-4, the maximum temperature of the outer surface of the PCGB-0 board decreased by 5.3℃, 5.6℃, 6.5℃, and 7.9℃ respectively, and the maximum temperature of the inner surface decreased by 3.7℃, 4.8℃, 5.4℃, and 7.2℃ respectively; the time difference from the outer surface temperature of PCGB-0 to the inner surface temperature rising to the highest was 644s, Compared with PCGB-0, the delay time of PCGB-1~PCGB-4 is increased by 35.6%, 55.9%, 66.5% and 78.5% respectively. It can be seen that the higher the content of composite phase change material in the plate, the greater the effect of delaying the highest temperature point, and the higher the highest temperature points on the inner and outer surfaces can be separated, which plays a role in regulating temperature across time, staggering the highest temperature point outside the wall and the highest temperature point on the inner surface, that is, also staggering the highest ambient temperature and the highest indoor temperature; with the increase of LA-HD-PA / DME content in the wall panel, more heat is stored in the wall panel, which can make the time interval between the highest temperature on the inner surface of the wall panel and the highest temperature in the model room longer, which is enough to show that the phase change wall panel with a higher content of composite phase change material has a better heat storage performance.
[0045] Although the embodiments of the present invention are described above in conjunction with the accompanying drawings, the present invention is not limited to the above specific embodiments and application fields, and the above specific embodiments are only illustrative and instructive, rather than restrictive. A person of ordinary skill in the art can also make many forms under the guidance of this specification and without departing from the scope of protection of the claims of the present invention, all of which belong to the protection of the present invention.
Claims
1. A method for preparing a phosphogypsum-based phase change energy storage wallboard, characterized in that: The method comprises the following steps: Step 1: Weigh lauric acid-hexadecanol-palmitic acid LA-HD-PA and modified diatomaceous earth DME according to a predetermined mass ratio; Step 2: placing the modified diatomaceous earth DME in a first temperature constant temperature dryer to a constant weight, heating the lauric acid-hexadecyl alcohol-palmitic acid LA-HD-PA solid to a liquid state and then adding the solid to the dried modified diatomaceous earth to form a mixture; Step 3: Stirring the mixture at a second temperature for a first predetermined time and then placing it in a vacuum drying oven for vacuum drying, and then taking it out and grinding it after a second predetermined time to obtain a diatomite-based shaped composite phase change material LA-HD-PA / DME; Step 4: Add the diatomite-based shaped composite phase change material LA-HD-PA / DME into phosphogypsum according to a predetermined mass ratio, and mix it with cement and fly ash to prepare a composite phase change energy storage gypsum board.
2. The method for preparing the phosphogypsum-based phase change energy storage wallboard according to claim 1, characterized in that: Preferably, the diatomaceous earth is subjected to calcination, acid washing and alkali washing to obtain modified diatomaceous earth.
3. The method for preparing the phosphogypsum-based phase change energy storage wallboard according to claim 1, characterized in that: The mixture was poured into a beaker, and the beaker containing the mixture was placed in a vacuum drying oven for vacuum drying. The vacuum drying oven was set at a temperature of 80° C. and a vacuum degree of 0.08 MPa.
4. A phosphogypsum-based phase change energy storage wallboard, characterized in that: It is made by the preparation method of the phosphogypsum-based phase change energy storage wallboard described in any one of claims 1 to 3.
5. The phosphogypsum-based phase change energy storage wallboard according to claim 4, characterized in that: It is used in building walls.
Citation Information
Cited By
Phase change gypsum board and production process thereof
CN121044878A